OP15 Early biliary complications after liver transplantation: incidence, risk factors and centre effect. (16th November 2010) - Dawwas, M; Gimson, A
Abstract : Introduction: Although biliary disease is one of the most common complications of liver transplantation, its incidence and risk factors have not been previously determined in a large risk-adjusted analysis. Method: Using the United Kingdom and Ireland Liver Transplant Database, we sought to identify the incidence of and independent risk factors for early biliary complications (EBC, defined as the occurrence of a biliary tract leak, or stricture either of which required endoscopic, percutaneous or surgical intervention or culminated in graft loss within the first 3 months after transplantation) among 7044 adult, orthotopic, single-organ liver transplants between March 1994 and February 2007. Univariate and multivariable logistic regression models were fitted to examine the association between EBC and a wide range of recipient, donor and graft risk factors. Results: The incidence of EBC in the cohort was 8.5%, of which 5.2% were strictures and 4.7% were bile leaks. Multivariable analysis identified the following independent risk factors for EBC: lower donor-recipient age difference (per year, OR 0.99 p<0.003), lower pre-transplant serum albumin (per g/dL, OR 0.84 p<0.009), higher pre-transplant serum bilirubin (per mg/dl, OR 1.01 p<0.008), longer cold ischaemia time (per hour, OR 1.04 p=0.01), negative donor rhesus antigen (OR 1.39 p<0.003), higher donor haemoglobin (per g/dl, OR 1.05 p<0.03), presence of donor urinary tract infection (OR 2.63 p<0.04), use of live (vs brain-dead) donors (OR 5.89 p<0.005) and utilisation of biliary stent vs duct-to-duct reconstruction (OR 2.22 p<0.03). In addition, 5 of the 8 transplant centres in the UK and Ireland experienced a significantly higher adjusted risk of EBC compared to the centre with the lowest incidence, the ORs ranging between 1.48 (p<0.02) and 3.76 (p<0.001). Conclusion: This multi-centre analysis, the largest reported to date, has identified several novel recipient, donor and graft risk factors that could be utilised to stratify the risk of EBC among patients undergoing liver transplantation. Significant variations exist among liver transplant centres in the risk of post-transplant biliary disease that cannot be accounted for by differences in recipient, donor or graft characteristics.